Contribuições do paradigma transdisciplinar para o ecoturismo - Kerlei Eniele Sonaglio (PASOS Revista de Turismo y Patrimonio Cultural, 2011)
The ecotourism is being planned based on different paradigms, especially the systemic paradigm. Despite the progress occurring in the planning and management of tourism since the 1950s, there is much to be improved, because various ecotourist interventions, especially in developing countries, has been unsuccessful, in terms of sustainability. In this article, will be presented transdisciplinary paradigm, characterized by “complexity”, and its contribution to the planning and management of ecotourism.